Program ikonograficzny wystroju wnętrza kościoła pw. Wniebowzięcia Najświętszej Maryi Panny i św. Augustyna w Kraśniku (wiek XVII i XVIII) - Czyż, Anna S. (Archiwa, Biblioteki i Muzea Kościelne, 2017)
Modern furnishings of the church dedicated to the Assumption of the Blessed Virgin Mary and St. Augustine in Kraśnik were created over three hundred years. However, the oldest trace of the decor from the 16th century is scant. In the first half of the 17th century they were exchanged, and it was at the time when the monastery in Kraśnik joined the Cracow Congregation. The 1630s were particularly important in the creation of the new decor of the church as the following things were founded: choir stalls, including collator ones, paintings by Dolabella as well as the high altar and brotherhood’s one. The above-mentioned elements of the interior were means of conveying the most important themes: canonic (Ordo apostolicus, the patrons of the Cracow Congregation), Passion, Eucharistic, Marian (including SalvatorMundi and MaterMisericordiae) as well as patronal. It cannot be ruled out that intensive artistic investment was connected with the plan to convene the General Chapter in Kraśnik in 1635. In the following decades, especially in the mid-eighteenth centuries, the interior was supplemented and developed, within the aforementioned themes, through the foundations of new altars, a pulpit and paintings in the chancel. Comparing the themes of the church decoration in Krasnik with other churches of the Canons Regular of the Cracow Congregation, it should be noted that they are typical. They referred to monastic life, including the spirituality of the canons and the "primacy" of the congregation, as well as the pastoral ministry being developed on the basis of Passion, Eucharistic and Marian themes. They were presented in the context of the changes taking place in the life of the Church after the Council of Trent, the trend which was also adopted by the Cracow Congregation of Corpus Christi, which co-created a new model of the sacred art in the Republic of Poland.